Investigating the Impact of Product Quality, Price Sensitivity, and Brand Reputation on Consumer Purchase Intentions in the FMCG Sector - Mamuaya, Nova Christian (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the intricate dynamics influencing consumer purchase intentions within the fast-moving consumer goods (FMCG) sector, focusing on the impact of product quality, price sensitivity, and brand reputation. A quantitative research design was adopted, with data collected from a sample of 500 respondents through an online survey. Descriptive statistics, correlation analysis, regression analysis, and ANOVA were employed to analyze the data comprehensively. The findings reveal a strong positive correlation between perceived product quality and consumer purchase intentions, emphasizing the importance of maintaining high-quality standards. Price sensitivity was found to negatively impact purchase intentions, highlighting the need for strategic pricing strategies. Brand reputation emerged as a significant predictor of purchase intentions, emphasizing the enduring value of strong brand equity. Demographic analyses identified distinct target segments based on age and income levels. The study contributes valuable insights for FMCG companies in developing tailored marketing strategies and enhancing market competitiveness.